MENGHAPUS ATAU MENETAPKAN HUKUMAN MATI? DARI TREN GLOBAL DAN LANDASAN POLITIK - Ecep Nurjamal (Siyasyatuna | Jurnal Hukum Tata Negara, 2024)
The death penalty is unlike any other punishment. Its continued existence in many countries of the world creates political tensions within these countries and between the governments of countries that retain and those that abolish the death penalty. After the Second World War, more and more countries abolished the death penalty. This article argues that the main determinant of this global trend towards abolition is political, a claim that finds support in a cross-country quantitative analysis from 1950 to 2002. Democracy, democratization, international political pressure on countries that still retain the death penalty, and peer group effects in relatively abolitionist regions all increase the likelihood of abolition. There is also a partisan effect, as abolition becomes more likely if the party of the chief executive is leftwing oriented. Cultural, social and economic determinants receive only limited support. The global trend towards abolition will continue if democracy continues to spread around the world and abolitionist countries stick to their commitment to push for abolition around the world..